The gestures of Hermes: Federico Fellini as an interpreter and circulating agent of images. Issue 1 (1st January 2021) - Pintor Iranzo, Ivan
Based on its relationship to comic books, this article proposes an iconographic study of the public figure of Federico Fellini in terms of the Hermes archetype. With the aim of explaining how Fellini's image has been interpreted from different visual perspectives, I consider two basic questions: what relationship does Fellini have to the images of himself and of Italian culture? And why have images in Fellini's films and his own public image been the object of constant reinterpretations in film, advertising and on social networks? Focusing on the rereading of Fellini's image in the comics of Milo Manara, this article explores a phenomenon that distinguishes Fellini's filmmaking: his role as a circulator of images of classical and popular culture out of the past and into the future. The figure of Hermes, the god of mediation, constitutes the archetype through which we can understand this central role of Fellini.